TINJAUAN YURIDIS PERJANJIAN KERJA TENAGA KERJA ASING PADA PT.TOYO KANETSU INDONESIA (STUDI PADA KAWASAN INDUSTRI BATU AMPAR, BATAM) - AYU FULIA SARI (PREMISE LAW JURNAL, 2013)
ABSTRACT The role of expatriates is very important for Indonesian national development as a country which is developing. In order to be able to compete in the free job market, Indonesia needs support and aid from foreign countries, including neighboring countries which is realized in the mutual agreement. The essential problem which arises in expatriates is our dependency on foreign investors. One of them is PT. Toyo Kanetsu which utilizes and employs expatriates; it is one of the foreign companies in Indonesia. Therefore, a work contract is needed between the company and the expatriates as it occurs in any contract in general. Keywords: Work Contract, Legal Protection, Expatriates